2020
DOI: 10.1080/13102818.2020.1814866
|View full text |Cite
|
Sign up to set email alerts
|

Puroindoline (Pina-D1 and Pinb-D1) and waxy (Wx-1) genes in Iranian bread wheat (Triticum aestivum L.) landraces

Abstract: Grain hardness and starch are two of the most important factors that determine the end-use quality of bread wheat (Triticum aestivum L.) grain. The grain hardness and amylose content are controlled by the puroindolines (Pina-D1 and Pinb-D1) genes, located on chromosomes 5D, and waxy (Wx-A1, -B1 and -D1) genes, located on chromosomes 7A, 4A and 7D. A total of 160 Iranian landraces from the Germplasm Bank of the International Maize and Wheat Improvement Center were evaluated for grain hardness using near infrare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 79 publications
3
3
0
Order By: Relevance
“…GPC is a parameter that is related to grain quality, but it is not significantly influenced by HMW-Gs subunits composition. We found a negligible correlation between GPC and SDSS (r = 0.074), which is in accordance with some authors [22,64,74], who showed that dough strength is independent of GPC, although the expression of a high-quality genotype requires enough protein content. The genetic components of GPC have been extensively studied in bread wheat [75][76][77][78], but GPC and yield are both largely influenced by environmental conditions (e.g., [79][80][81]).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…GPC is a parameter that is related to grain quality, but it is not significantly influenced by HMW-Gs subunits composition. We found a negligible correlation between GPC and SDSS (r = 0.074), which is in accordance with some authors [22,64,74], who showed that dough strength is independent of GPC, although the expression of a high-quality genotype requires enough protein content. The genetic components of GPC have been extensively studied in bread wheat [75][76][77][78], but GPC and yield are both largely influenced by environmental conditions (e.g., [79][80][81]).…”
Section: Discussionsupporting
confidence: 92%
“…In this work, correlations between traits showed a high and negative correlation between GPC and TKW. A negative correlation between both traits has been found in other studies [64]. Traditionally, high-grain-yielding varieties have been associated with lower-quality parameters, mainly because of the inverse relationship between protein content and grain yield [14,15,94].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Different studies detected mutation in purindoline (Pina and Pinb) genes using other techniques, i.e. STS-allele-specific markers, cleaved amplified polymorphic sequences (CAPS), SNP assays and pyrosequencing (Maryami, Azimi, Guzman, Dreisigacker, & Najafian, 2020;Przyborowski, Gasparis, Kała, Orczyk, & Nadolska-Orczyk, 2020). A genomic study of puroindoline alleles revealed that the Pina gene could not be expressed in hard textured wheat as exhibiting mutation in the Pina gene.…”
Section: Introductionmentioning
confidence: 99%